(untitled) (European Journal of Education and Psychology, 2011)
This study aims to determine, first, what are the reasons that lead young people to abandon physical and sport practice and, secondly, to discover why some young people never started in this type of experience, in order to establish an educational philosophy that involves the physical and sport practice of young people and that they optimize both their beginning and their maintenance in this lifestyle. This research is based on methodological triangulation with quantitative techniques such as descriptive analysis of data collected through a questionnaire and qualitative techniques, such as content analysis of four focus groups. The lack of interest is set as the main barrier to start or stay in physical and sports practice both in students of secondary school and in college students. Therefore, certain education key are proposals to be considered at an early age, to increase motivation among the population, in general, and physically inactive youth in particular.